Manufacturing method for all-solid-state batteries

The proposed manufacturing method for all-solid-state batteries, involving a laminate structure and sequential rolling presses, addresses the issue of electrode undulations and resulting battery resistance, achieving improved performance and productivity.

JP7647456B2Active Publication Date: 2025-03-18TOYOTA JIDOSHA KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021146569
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-09
Publication Date
2025-03-18
Estimated Expiration
2041-09-09

AI Technical Summary

Technical Problem

Existing methods for manufacturing all-solid-state batteries result in electrode undulations during densification pressing, leading to increased battery resistance.

Method used

A manufacturing method involving a laminate structure with a positive electrode, solid electrolyte layer, and negative electrode, followed by a first rolling press from one direction and a second rolling press from a perpendicular direction to suppress electrode undulations.

Benefits of technology

This method effectively reduces battery resistance in all-solid-state batteries by minimizing electrode undulations and improving the accuracy of the stacking position, thereby enhancing productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647456000002
    Figure 0007647456000002
  • Figure 0007647456000001
    Figure 0007647456000001
Patent Text Reader

Abstract

To provide an all-solid battery with low battery resistance.SOLUTION: A manufacturing method of an all-solid battery includes a step of preparing a laminate in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order, a first pressing step of roll-pressing the laminate from one direction, and a second pressing step of roll-pressing the laminate after the first pressing step from a direction orthogonal to the one direction.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for manufacturing an all-solid-state battery. [Background technology]

[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. In the automobile industry, too, development of high-output, high-capacity batteries for electric vehicles or hybrid vehicles is underway. Moreover, all-solid-state batteries have attracted attention because they use a solid electrolyte as the electrolyte between the positive electrode and the negative electrode instead of an electrolytic solution containing an organic solvent.

[0003] Patent Document 1 discloses a method for producing an all-solid-state battery, in which an electrode mixture is transferred, densified by pressing, and then the electrodes are cut.

[0004] Patent Document 2 discloses a method for manufacturing a battery in which uncoated and coated parts of an electrode sheet are roll-pressed.

[0005] Patent Document 3 discloses a method for producing an all-solid-state battery, in which electrode mixtures are laminated and then roll-pressed. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2020-161471 A [Patent Document 2] JP 5760366 A [Patent Document 3] JP 2020-126800 A Summary of the Invention [Problem to be solved by the invention]

[0007] In conventional technology, electrode waviness caused by densification pressing increases the battery resistance of all-solid-state batteries.

[0008] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide an all-solid-state battery having low battery resistance. [Means for solving the problem]

[0009] The method for producing an all-solid-state battery according to the present disclosure includes the steps of: preparing a laminate in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order; A first pressing step of roll-pressing the laminate from one direction; The method further comprises a second press process in which the laminate after the first press process is roll-pressed in a direction perpendicular to the one direction. Effect of the Invention

[0010] The present disclosure can suppress the occurrence of electrode waviness and reduce the battery resistance of an all-solid-state battery. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a flowchart showing an example of a method for producing an all-solid-state battery according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The method for producing an all-solid-state battery according to the present disclosure includes the steps of: preparing a laminate in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order; A first pressing step of roll-pressing the laminate from one direction; The method further comprises a second press process in which the laminate after the first press process is roll-pressed in a direction perpendicular to the one direction.

[0013] The electrode is stretched and wrinkled by rolling in the conveying direction by the densification press of the laminate. These wrinkles hinder the interface contact with the current collector, leading to a decrease in the electrical performance of the battery. In addition, the electrode wrinkles deteriorate the accuracy of the stacking position, which may lead to a decrease in productivity. In the present disclosure, after the laminate is densified by pressing, the laminate is densified under appropriate conditions in a direction perpendicular to the densification press conveying direction, i.e., the laminate is densified under appropriate conditions in the width direction of the laminate rotated 90° left or right from the densification press conveying direction. It is presumed that when the laminate is densified by pressing, a large elongation occurs in the conveying direction, which causes the laminate to shrink in the width direction, resulting in electrode wrinkles. Since wrinkles occur due to the difference in elongation rate between the conveying direction and the width direction, by densifying the laminate in the width direction to compensate for the shrinkage, the elongation rate in the conveying direction and the width direction can be matched, thereby suppressing the occurrence of electrode wrinkles.

[0014] The method for producing an all-solid-state battery according to the present disclosure includes (1) a preparation step, (2) a first pressing step, and (3) a second pressing step. FIG. 1 is a flowchart showing an example of a method for producing an all-solid-state battery according to the present disclosure.

[0015] (1) Preparation process The preparation step is a step of preparing a laminate in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order. The laminate may be a laminate in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order, or a laminate in which a positive electrode layer, a solid electrolyte layer, and a negative electrode layer are laminated in this order, or a laminate in which a positive electrode current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector are laminated in this order, or a laminate in which a positive electrode layer, a solid electrolyte layer, a negative electrode layer, a negative electrode current collector, a negative electrode layer, a solid electrolyte layer, and a positive electrode layer are laminated in this order, or a laminate in which a positive electrode current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, a negative electrode current collector, a negative electrode layer, a solid electrolyte layer, a positive electrode layer, and a positive electrode current collector are laminated in this order.

[0016] [Positive electrode] The positive electrode includes a positive electrode layer and, optionally, a positive electrode current collector.

[0017] [Positive electrode layer] The positive electrode layer contains a positive electrode active material, and may contain optional components such as a solid electrolyte, a conductive material, and a binder.

[0018] There is no particular limitation on the type of positive electrode active material, and any material that can be used as an active material for an all-solid-state battery can be used. Examples of the positive electrode active material include metallic lithium (Li), lithium alloys, LiCoO2, and LiNi. 0.8 Co 0.15 Al 0.05 O2, LiNi x Co 1-x O2(0 <x<1)、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Examples of the Li-Mn spinel substituted with a different element include LiO2, LiMnO2, Li-Mn spinel substituted with a different element, lithium titanate, lithium metal phosphate, LiCoN, Li2SiO3, and Li4SiO4, transition metal oxides, TiS2, Si, SiO2, Si alloys, and lithium-storing intermetallic compounds. The Li-Mn spinel substituted with a different element is, for example, LiMn 1.5 Ni 0.5 O4, LiMn 1.5 Al 0.5 O4, LiMn 1.5 Mg 0.5 O4, LiMn 1.5 Co 0.5 O4, LiMn 1.5 Fe 0.5 O4 and LiMn 1.5 Zinc 0.5 O4, etc. Lithium titanate is, for example, Li4Ti5O 12 The lithium metal phosphates are, for example, LiFePO4, LiMnPO4, LiCoPO4, and LiNiPO4. The transition metal oxides are, for example, V2O5, and MoO3. The lithium storage intermetallic compounds are, for example, Mg2Sn, Mg2Ge, Mg2Sb, and Cu3Sb. Examples of lithium alloys include Li-Au, Li-Mg, Li-Sn, Li-Si, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Ru, Li-Rh, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, and Li-At. Examples of Si alloys include alloys with metals such as Li, and may also be alloys with at least one metal selected from the group consisting of Sn, Ge, and Al. The shape of the positive electrode active material is not particularly limited, and may be particulate. When the positive electrode active material is particulate, the positive electrode active material may be primary particles or secondary particles. A coating layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material, because this can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of Li-ion conductive oxides include LiNbO3 and Li4Ti5O 12 , and Li3PO4. The thickness of the coating layer is, for example, 0.1 nm or more, and may be 1 nm or more. Meanwhile, the thickness of the coating layer is, for example, 100 nm or less, and may be 20 nm or less. The coverage of the coating layer on the surface of the positive electrode active material is, for example, 70% or more, and may be 90% or more.

[0019] As the solid electrolyte, the same ones as those exemplified in the solid electrolyte layer can be exemplified. The content of the solid electrolyte in the positive electrode layer is not particularly limited, but may be, for example, within a range of 1 mass % to 80 mass % when the total mass of the positive electrode layer is taken as 100 mass %.

[0020] The conductive material may be a known material, such as a carbon material and metal particles. The carbon material may be at least one selected from the group consisting of acetylene black, furnace black, VGCF, carbon nanotubes, and carbon nanofibers. In particular, from the viewpoint of electronic conductivity, at least one selected from the group consisting of VGCF, carbon nanotubes, and carbon nanofibers may be used. The metal particles may be particles of Ni, Cu, Fe, SUS, etc. The content of the conductive material in the positive electrode layer is not particularly limited.

[0021] Examples of the binder include acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), styrene butadiene rubber (SBR), etc. The content of the binder in the positive electrode layer is not particularly limited.

[0022] The thickness of the positive electrode layer is not particularly limited.

[0023] The positive electrode layer can be formed by a conventionally known method. For example, a positive electrode active material and, if necessary, other components are put into a solvent and stirred to prepare a positive electrode layer slurry, and the positive electrode layer slurry is applied onto one side of a support such as a positive electrode current collector and dried to obtain a positive electrode layer. Examples of the solvent include butyl acetate, butyl butyrate, mesitylene, tetralin, heptane, and N-methyl-2-pyrrolidone (NMP). The method for applying the positive electrode layer slurry onto one surface of a support such as a positive electrode current collector is not particularly limited, and examples thereof include a doctor blade method, a metal mask printing method, an electrostatic application method, a dip coating method, a spray coating method, a roll coating method, a gravure coating method, and a screen printing method. The support can be appropriately selected from those having self-supporting properties and is not particularly limited. For example, metal foils such as Cu and Al can be used.

[0024] As another method for forming the positive electrode layer, the positive electrode layer may be formed by pressure molding a powder of a positive electrode mixture containing a positive electrode active material and other components as necessary. When the powder of the positive electrode mixture is pressure molded, a press pressure of about 1 MPa to 2000 MPa is usually applied. The method of applying pressure is not particularly limited, but examples thereof include a method of applying pressure using a plate press, a roll press, or the like.

[0025] [Positive electrode current collector] The positive electrode current collector may be a known metal that can be used as a current collector for an all-solid-state battery. Examples of such metals include metal materials containing one or more elements selected from the group consisting of Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Co, Cr, Zn, Ge, and In. Examples of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. The shape of the positive electrode current collector is not particularly limited, and may be in various shapes such as a foil shape, a mesh shape, etc. The thickness of the positive electrode current collector varies depending on the shape, but may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.

[0026] [Negative electrode] The negative electrode includes a negative electrode layer and, optionally, a negative electrode current collector.

[0027] [Negative electrode layer] The negative electrode layer contains at least a negative electrode active material, and optionally contains a solid electrolyte, a conductive material, a binder, and the like. The negative electrode active materials include graphite, mesocarbon microbeads (MCMB), highly oriented graphite (HOPG), hard carbon, soft carbon, lithium alone, lithium alloy, Si alone, Si alloy, and Li4Ti5O 12 As the lithium alloy and the Si alloy, the same ones as those exemplified in the positive electrode active material can be used. The shape of the negative electrode active material is not particularly limited, and examples thereof include a particulate shape, a plate shape, etc. When the negative electrode active material is particulate, the negative electrode active material may be primary particles or secondary particles. The conductive material and binder used in the negative electrode layer may be the same as those exemplified in the positive electrode layer. The solid electrolyte used in the negative electrode layer may be the same as those exemplified in the solid electrolyte layer. The thickness of the negative electrode layer is not particularly limited, but may be, for example, 10 to 100 μm. The content of the negative electrode active material in the negative electrode layer is not particularly limited, and may be, for example, 20% by mass to 90% by mass.

[0028] [Negative electrode current collector] The material of the negative electrode current collector may be a material that does not alloy with Li, and examples thereof include SUS, copper, and nickel. Examples of the form of the negative electrode current collector include foil and plate. The planar shape of the negative electrode current collector is not particularly limited, and examples thereof include a circle, an ellipse, a rectangle, and any polygonal shape. The thickness of the negative electrode current collector varies depending on the shape, and may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.

[0029] [Solid electrolyte layer] The solid electrolyte layer includes at least a solid electrolyte. As the solid electrolyte contained in the solid electrolyte layer, any known solid electrolyte that can be used in an all-solid-state battery can be appropriately used, and examples of such solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes. Examples of sulfide-based solid electrolytes include Li2S-P2S5, Li2S-SiS2, LiX-Li2S-SiS2, LiX-Li2S-P2S5, LiX-Li2O-Li2S-P2S5, LiX-Li2S-P2O5, LiX-Li3PO4-P2S5, and Li3PS4. The above description of "Li2S-P2S5" means a material made using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions. In addition, "X" in the above LiX indicates a halogen element. The raw material composition containing LiX may contain one type or two or more types of LiX. When two or more types of LiX are contained, the mixing ratio of the two or more types is not particularly limited. The molar ratio of each element in the sulfide-based solid electrolyte can be controlled by adjusting the content of each element in the raw material. The molar ratio and composition of each element in the sulfide-based solid electrolyte can be measured, for example, by ICP emission spectrometry.

[0030] The sulfide-based solid electrolyte may be a sulfide glass, a crystallized sulfide glass (glass ceramics), or a crystalline material obtained by subjecting a raw material composition to a solid-phase reaction treatment. The crystalline state of the sulfide-based solid electrolyte can be confirmed, for example, by subjecting the sulfide-based solid electrolyte to powder X-ray diffraction measurement using CuKα radiation.

[0031] The sulfide glass can be obtained by subjecting a raw material composition (e.g., a mixture of Li2S and P2S5) to an amorphous process, such as mechanical milling.

[0032] Glass ceramics can be obtained, for example, by heat treating a sulfide glass. The heat treatment temperature may be any temperature higher than the crystallization temperature (Tc) of the sulfide glass observed by thermal analysis, and is usually 195° C. or higher. On the other hand, there is no particular upper limit to the heat treatment temperature. The crystallization temperature (Tc) of the sulfide glass can be measured by differential thermal analysis (DTA). The heat treatment time is not particularly limited as long as the desired crystallinity of the glass ceramic is obtained, but is, for example, within the range of 1 minute to 24 hours, and particularly within the range of 1 minute to 10 hours. The method of heat treatment is not particularly limited, but may be, for example, a method using a baking furnace.

[0033] Examples of oxide-based solid electrolytes include substances having a garnet-type crystal structure containing, for example, Li, La, A (A is at least one of Zr, Nb, Ta, and Al), and O. 3+x PO 4-x N x (1≦x≦3), etc.

[0034] The solid electrolyte may be in the form of particles from the viewpoint of ease of handling.

[0035] The solid electrolyte may be used alone or in combination of two or more kinds. When two or more kinds of solid electrolytes are used, the two or more kinds of solid electrolytes may be mixed, or two or more layers of the solid electrolyte may be formed to form a multilayer structure. The proportion of the solid electrolyte in the solid electrolyte layer is not particularly limited, but is, for example, 50% by mass or more, may be in the range of 60% by mass or more and 100% by mass or less, may be in the range of 70% by mass or more and 100% by mass or less, or may be 100% by mass.

[0036] The solid electrolyte layer may contain a binder from the viewpoint of expressing plasticity, etc. Examples of such binders include the materials exemplified as the binders used in the positive electrode layer. However, in order to facilitate high output, the binder may be contained in the solid electrolyte layer in an amount of 5 mass% or less from the viewpoint of preventing excessive aggregation of the solid electrolyte and enabling the formation of a solid electrolyte layer having a uniformly dispersed solid electrolyte.

[0037] The thickness of the solid electrolyte layer is not particularly limited, and is usually 0.1 μm or more and 1 mm or less. The method for forming the solid electrolyte layer includes a method of pressing a powder of a solid electrolyte material containing a solid electrolyte, etc. When pressing the powder of the solid electrolyte material, a press pressure of about 1 MPa or more and 2000 MPa or less is usually applied. The method of applying pressure is not particularly limited, but may be any of the pressure applying methods exemplified in the formation of the positive electrode layer.

[0038] (2) First pressing process The first pressing step is a step of performing roll pressing on the laminate from one direction. The one direction may be any direction of transport when the laminate is placed on a roll press machine and transported. The laminate is roll-pressed from one direction to apply a press pressure in the stacking direction (vertical direction) of the laminate, thereby pressure-molding the laminate. The roll pressing may be carried out using a known roll pressing machine or the like. The pressing pressure during roll pressing is not particularly limited and may be, for example, 1 ton / cm or more, 2 ton / cm or more, 3 ton / cm or more, 4 ton / cm or more, 5 ton / cm or more, or 6 ton / cm or more, and may be 10 ton / cm or less, 8 ton / cm or less, 7 ton / cm or less, or 6 ton / cm or less. The temperature during roll pressing is not particularly limited, and may be, for example, 50° C. or more, 100° C. or more, 120° C. or more, 150° C. or more, 170° C. or more, 190° C. or more, or 200° C. or more, or 250° C. or less, 230° C. or less, or 210° C. or less. The roll pressing may also be performed at room temperature.

[0039] (3) Second pressing process The second pressing step is a step of roll pressing the laminate after the first pressing step in a direction perpendicular to the one direction, which stretches out the electrode wrinkles generated in the first pressing step and suppresses the generation of electrode wrinkles. The direction perpendicular to one direction may be a direction in which the laminate is rotated 90° in the planar direction (left-right direction) of the laminate with respect to any transport direction when the laminate is placed on a roll press machine and transported, or it may be the width direction of the laminate. By roll pressing the laminate from a direction rotated 90° to the left or right of an arbitrary conveying direction, a press pressure is again applied to the laminate in the stacking direction (vertical direction) and the occurrence of electrode wrinkles is suppressed. The pressing pressure and pressing temperature in the second pressing step can be higher than those exemplified in the first pressing step, and may be the same as or different from those in the first pressing step.

[0040] The all-solid-state battery of the present disclosure may be the above-described laminate. The all-solid-state battery may have only one of the laminates described above, or may be formed by laminating a plurality of the laminates. The all-solid-state battery may be a primary battery or a secondary battery, but may be a secondary battery. The secondary battery can be repeatedly charged and discharged. The secondary battery is useful, for example, as an in-vehicle battery. The all-solid-state battery may be an all-solid-state lithium secondary battery or an all-solid-state lithium ion secondary battery. Examples of the shape of the all-solid-state battery include a coin type, a laminate type, a cylindrical type, and a square type. EXAMPLES

[0041] Example 1 The following materials were used for the positive electrode current collector, the positive electrode layer, the solid electrolyte layer, the negative electrode layer, and the negative electrode current collector. Positive electrode current collector: Aluminum foil (thickness t=15μm) ·Positive electrode layer: LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 / sulfide-based solid electrolyte / PVdF (binder) = 80:15:5wt% ·Solid electrolyte layer: Sulfide-based solid electrolyte Negative electrode layer: Si / sulfide-based solid electrolyte / SBR (binder) = 50:48:2wt% Negative electrode current collector: Cu foil (thickness t=15μm)

[0042] (1) Preparation process A slurry containing a material for forming the positive electrode layer was applied onto a transfer substrate (aluminum foil) and dried to form a positive electrode layer with the transfer substrate. Furthermore, a slurry containing materials for forming a solid electrolyte layer was applied onto a transfer substrate (aluminum foil) and dried to form a solid electrolyte layer with a transfer substrate. Meanwhile, a slurry containing a material for forming a negative electrode layer was applied to both sides of a negative electrode current collector (Cu foil) and dried to form a negative electrode layer on both sides of the negative electrode current collector. Then, the solid electrolyte layer formed on the transfer substrate was transferred to both sides of the negative electrode layer formed on both sides of the negative electrode current collector, thereby forming a "solid electrolyte layer-negative electrode layer-negative electrode current collector-negative electrode layer-solid electrolyte layer" laminate. Next, the positive electrode layer with the transfer substrate was attached to both sides of the "solid electrolyte layer-negative electrode layer-negative electrode current collector-negative electrode layer-solid electrolyte layer" laminate so that the positive electrode layer and the solid electrolyte layer were in direct contact with each other, and the positive electrode layer was laminated at a pressure of 1 ton / cm 2 It was pressed with a pressure of . Finally, the transfer substrate for the positive electrode layer was removed, and a laminate (positive electrode layer-solid electrolyte layer-negative electrode layer-negative electrode current collector-negative electrode layer-solid electrolyte layer-positive electrode layer) was obtained, which was to be compacted by a roll press. (2) First pressing process The laminate "cathode layer-solid electrolyte layer-negative electrode layer-negative electrode current collector-negative electrode layer-solid electrolyte layer-cathode layer" obtained in the above preparation step was heated to 170°C and roll pressed in one direction (the conveying direction of the laminate) at 5 ton / cm. (3) Second pressing process The laminate that had been subjected to the first pressing step was roll pressed at 4 ton / cm in a direction perpendicular to the one direction (the width direction of the laminate) while being heated to 170°C. Thereafter, the negative electrode layer was cut to have a protruding portion, and a positive electrode current collector (Al foil) was attached to both sides of the laminate that had been subjected to the second pressing step using a binder, thereby producing the all-solid-state battery of Example 1.

[0043] Example 2 An all-solid-state battery was produced in the same manner as in Example 1, except that in the above (3) second pressing step, roll pressing was performed at 5 ton / cm.

[0044] Example 3 An all-solid-state battery was produced in the same manner as in Example 1, except that in the above (3) second pressing step, roll pressing was performed at 3 ton / cm.

[0045] Comparative Example 1 An all-solid-state battery was produced in the same manner as in Example 1, except that the above (3) second pressing step was not performed.

[0046] The all-solid-state batteries produced in Examples 1 to 3 and Comparative Example 1 were evaluated as follows. Presence or absence of wrinkles (visual inspection): A visual inspection was carried out to check the direction and presence or absence of wrinkles. Resistance measurement: Discharge was performed under the conditions of 25° C., SOC 50%, 1C, 2 sec., and the resistance reduction rate was calculated from the following formula when Comparative Example 1 was taken as 100%. Resistance reduction rate (%)=(resistance value of each level in Examples 1 to 3 and Comparative Example 1 / resistance value of Comparative Example 1)*100

[0047] [Table 1]

[0048] [Evaluation Results] As shown in Table 1, it is understood that the battery resistances of Examples 1 to 3 are lower than that of Comparative Example 1. Examples 2 and 3 had a greater effect of reducing resistance than Comparative Example 1, which did not have a width-direction press, but the resistance reduction rate was smaller than Example 1. It is presumed that the width-direction press in Example 2 was slightly stronger, which caused new wrinkles in the conveying direction, resulting in a smaller resistance reduction rate. It is presumed that the width-direction press in Example 3 was slightly weaker, which left some wrinkles, resulting in a smaller resistance reduction rate.

Claims

1. A method for producing an all-solid-state battery, comprising: preparing a laminate in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order; A first pressing step of roll-pressing the laminate at 5 ton / cm from one direction while heating the laminate at 170°C; and a second pressing step of roll-pressing the laminate after the first pressing step at 3 ton / cm to 5 ton / cm in a direction perpendicular to the one direction while heating the laminate to 170°C.

2. The method for manufacturing an all-solid-state battery described in claim 1, wherein the second pressing step is a step of roll pressing the laminate after the first pressing step at 4 ton / cm in a direction perpendicular to the one direction while heating the laminate to 170°C.

Citation Information

Patent Citations

  • Language teaching device

    JP1982060366A

  • Bipolar type secondary battery

    JP2008097940A

  • Bipolar battery and its manufacturing method

    JP2008166256A

  • All solid state battery and manufacturing method thereof

    JP2020126800A

  • Manufacturing method of all-solid battery, and all-solid battery

    JP2020161471A